Quality and safety of genetic testing in Australia and New Zealand: A review of the current regulatory framework - Goold, I; Pearn, A; Bettiol, S; Ballantyne, A (2006)
This paper provides an overview of the regulation of quality assurance for genetic testing in Australia and New Zealand and outlines the steps currently being taken to critically appraise and improve the regulatory framework in each country. It aims to contextualize this framework within the broader context of quality and patient safety concerns; and to draw together the concerns and recommendations of the various organizations that have been working to improve quality assurance in this area. © 2006 Goold et al; licensee BioMed Central Ltd.